Divergence in Antiviral Activities of Carbon Dots versus Nano-Carbon/Organic Hybrids and Implications - Cristian E. Rodriguez; Audrey F. Adcock; Buta Singh; Subhadra Yerra; Yongan Tang; Ya-Ping Sun; Liju Yang (C, 2023)
Carbon dots (CDots) are generally defined as small carbon nanoparticles (CNPs) with effective surface passivation, for which the classical synthesis is the functionalization of pre-existing CNPs with organic molecules. However, “dot” samples produced by “one-pot” thermal carbonization of organic precursors are also popular in the literature. These carbonization-produced samples may contain nano-carbon domains embedded in organic matters from the precursors that survived the thermal processing, which may be considered and denoted as “nano-carbon/organic hybrids”. Recent experimental evidence indicated that the two different kinds of dot samples are largely divergent in their photo-induced antibacterial functions. In this work, three representative carbonization-produced samples from the precursor of citric acid–oligomeric polyethylenimine mixture with processing conditions of 200 °C for 3 h (CS200), 330 °C for 6 h (CS330), and microwave heating (CSMT) were compared with the classically synthesized CDots on their photo-induced antiviral activities. The results suggest major divergences in the activities between the different samples. Interestingly, CSMT also exhibited significant differences between antibacterial and antiviral activities. The mechanistic origins of the divergences were explored, with the results of different antimicrobial activities among the hybrid samples rationalized in terms of the degree of carbonization in the sample production and the different sample structural and morphological characteristics.